THE INFLUENCE OF COMPENSATION AND JOB CHARACTERISTICS ON EMPLOYEE JOB SATISFACTION PRODUCTION UNIT - Arifin, Syamsul; Liftiana, Rika (CV Pena Jaya Pers, 2024)
This research was conducted to know the influence of variables compensation and job characteristics on the work satisfaction of Production Unit employees at PT. Cemerlang. This research is causality research and the method used in this research is survey. The number of samples are 93 respondents and data collecting is conducted by filling out some questionaires. There are two groups of variables in this research. Those are independent variables which are compensation and job characteristics, and the other is dependent variable which is work satisfaction of Production Unit employees at PT. Cemerlang. Multiple linear regression is used to analyze the influence of variables compensation and job characteristics on the work satisfaction. According to the results of regression analysis, find that simultaneously variables of compensation and job characteristics have significant effects on work satisfaction of production unit employees at PT. Cemerlang . Partially, the variable of job characteristic which is autonomy of job (X3) has the most dominant effect on work satisfaction of production unit employees at PT. Cemerlang.